Heat‐tolerant Flowering Plants of Active Geothermal Areas in Yellowstone National Park - STOUT, RICHARD G. (Ann Bot, 2002)
A broad survey of most of the major geyser basins within Yellowstone National Park (Wyoming, USA) was conducted to identify the flowering plants which tolerate high rhizosphere temperatures (≥40 °C) in geothermally heated environments. Under such conditions, five species of monocots and four species of dicots were repeatedly found. The predominant flowering plants in hot soils (>40 °C at 2–5 cm depth) were grasses, primarily Dichanthelium lanuginosum. Long‐term (weeks to months) rhizosphere temperatures of individual D. lanuginosum above 40 °C were recorded at several different locations, both in the summer and winter. The potential role of heat shock proteins (HSPs) in the apparent adaptation of these plants to chronically high rhizosphere temperatures was examined. Antibodies to cytoplasmic class I small heat shock proteins (sHSPs) and to HSP101 were used in Western immunoblot analyses of protein extracts from plants collected from geothermally heated soils. Relatively high levels of proteins reacting with anti‐sHSP antibodies were consistently detected in root extracts from plants experiencing rhizosphere temperatures above 40 °C, though these proteins were usually not highly expressed in leaf extracts from the same plants. Proteins reacting with antibodies to HSP101 were also present both in leaf and root extracts from plants collected from geothermal soils, but their levels of expression were not as closely related to the degree of heat exposure as those of sHSPs.